FDI in least developed countries at a glance : 2002 (UN New YorkUS, 2002)
Depicts recent trends in FDI to least developed countries and changes that have taken place in relevant areas of the regulatory legal framework. Presents country profiles for each of the 49 least developed countries, hereby providing a general picture of the role of FDI in these countries. Provides basic information on the volume and significance of FDI in least developed countries.
Keywords: FOREIGN INVESTMENT